The Potential of Ethanol Extract of Jasmine Flowers (Jasminum sambac L.) as a Repellent Against Houseflies (Musca domestica) - yauwan tobing lukiyono; Irwan Sulistio; Agus Aan Adriansyah; fadhilatul ilmia (Universitas Nahdlatul Ulama Surabaya, 2026)
This research is based on the need for environmentally friendly alternatives to chemical insecticides. To determine the potential of ethanol extract of jasmine flowers (Jasminum sambac L.) as a repellent against houseflies (Musca domestica). The study employed a post-test only control group design with ethanol extract concentrations of 15%, 20%, and 25%, along with a positive control (Venox fly repellent spray) and a negative control (distilled water). The effectiveness was assessed by counting the number of flies that landed and were repelled. Data were analyzed using probit regression to determine the ED₅₀ and ED₉₉ values. Higher extract concentrations resulted in stronger repellent effects. A 15% concentration produced a repellency rate of 34.37%, 20% achieved 51.64%, and 25% reached 80.61%. The ED₅₀ was found at 16.494%, and the ED₉₉ at 38.222%. Ethanol extract of jasmine flowers has the potential to serve as an effective natural bioinsecticide for controlling houseflies.